Harnessing the private health sector by using prices as a policy instrument: Lessons learned from South Africa. Issue 5 (May 2018) - Barber, Sarah L.; Kumar, Ankit; Roubal, Tomas; Colombo, Francesca; Lorenzoni, Luca
Highlights: Health policy-makers strive to harness resources and efficiency gains from the private sector while addressing market failures. South Africa spends 43% of total health spending on private voluntary health insurance covering only 16% of the population. Price levels in the South African private hospital sector are very high relative to its income, placing specialized resources out of the reach of most people. Given that the public and the private sectors draw on the same pool of resources, prices are a key policy lever. The cautionary lesson is the importance of norms and institutions that uphold price schedules and price determination in high-income countries. Abstract: Governments frequently draw upon the private health care sector to promote sustainability, optimal use of resources, and increased choice. In doing so, policy-makers face the challenge of harnessing resources while grappling with the market failures and equity concerns associated with private financing of health care. The growth of the private health sector in South Africa has fundamentally changed the structure of health care delivery. A mutually reinforcing ecosystem of private health insurers, private hospitals and specialists has grown to account for almost half of the country's spending on health care, despite only serving 16% of the population with the capacity to pay. Following years of consolidation among private hospital groups and insurance schemes, and after successive failures at establishing credible price benchmarks, South Africa's private hospitals charge prices comparable with countries that are considerably richer. This compromises the affordability of a broad-based expansion in health care for the population. The South African example demonstrates that prices can be part of a structure that perpetuates inequalities in access to health care resources. The lesson for other countries is the importance of norms and institutions that uphold price schedules in high-income countries. Efforts to compromise or liberalize price setting should be undertaken with a healthy degree of caution.